Maternal and Renal Outcome Of Pregnancy Related Acute Kidney Injury Requiring Dialysis in a Tertiary Care Centre - Hossain, Md Shahadat; Anwar, SM Imrul; Morshed, Abu Sayed Mohammad; Musharraf, Ishtiaque; Majumder, Ariful Islam; Huq, Afroza (Journal of Dhaka Medical College, 2023)
Introduction: Acute kidney injury (AKI) is a rare complication of pregnancy, but may be associated with significant morbidity and mortality in young and often otherwise healthy women. In a developing countries like Bangladesh due to low resource settings intermittent hemodialysis is the usual mode of renal replacement therapy. It opens up a field of investigation to assess the maternal and renal outcome of pregnancy associated acute kidney injury after getting dialysis. Materials and method: This analytic, descriptive, prospective study was performed over 46 patients with pregnancy associated AKI requiring dialysis during July 2015 to June 2016. Etiology and spectrum of pregnancy related acute kidney injury (PR - AKI) requiring dialysis were assessed and maternal and renal outcome were analyzed. Result : Puerperal sepsis(25, 54.3%) was the most prevalent cause, followed by preeclampsia/ eclampsia, (7,15.2%), septic abortion ( 5 ,10.9%), PPH/APH (5 ,10.9%), sepsis with PPH (2 ,4.3%), HELLP syndrome (1 ,2.2%) and sepsis with HELLP (1 ,2.2%)36 (73.3%) patients remained alive and 10 (22.8%) patients expired. HELLP syndrome and maternal mortality was more commonly observed in dialysis requiring group. Delivery at term was more commonly observed in dialysis requiring group and preterm delidery was more common in dialysis not requiring group. 26(56.5%) patients had delivery at term , 15(32.6%) had preterm delivery and abortion was found in 5(10.9%). Renal out come was better in dialysis not requiring group when compared with dialysis requiring group.Complete recovery was found in 19(52.8%) patient at 3 months follow up, 10(27.8%) had partial recovery seven patients remained dialysis dependent. According to the RIFLE criteria,19 patients were in the Injury category and 27 patients were in the Failure category.Relative risk of mortality in Injury is 0.94 and in Failure is 1.05. Multivariate logistic regression analysis showed that RIFLE classification did not discriminate the prognosis ( p value 0.788) in pregnancy associated AKI requiring dialysis. Conclusion : PR- AKI requiring dialysis is associated with high maternal mortality and poor renal outcome. J Dhaka Med Coll. 2021; 30(2) : 202-207